2022
DOI: 10.18231/j.ijogr.2022.003
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous ferric carboxymaltose versus iron sucrose in iron deficiency anemia of pregnancy

Abstract: Iron deficiency is the most common nutritional deficiency worldwide. Anemia, defined by the World Health Organization as hemoglobin < 11 g/dl, is frequently seen in the antenatal period and affects 4-48% of women who give birth and severe anemia, with hemoglobin levels <9 g/dl .This study is to evaluate the efficacy and safety of intravenous Ferric Carboxymaltose. (FCM) in comparison with intravenous Iron sucrose complex (ISC) for treatment of iron deficiency anemia in pregnancy.: A comparative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…In a study done by Khatun F et al [10] , they found that the adverse reactions was lower among patients of FCM than iron sucrose. In a study done by Parikh A et al [11] , the adverse events were all mild and quickly reversible and mostly restricted to local reaction at the infusion site in both the treatment groups. These findings are comparable with the findings of the present study.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…In a study done by Khatun F et al [10] , they found that the adverse reactions was lower among patients of FCM than iron sucrose. In a study done by Parikh A et al [11] , the adverse events were all mild and quickly reversible and mostly restricted to local reaction at the infusion site in both the treatment groups. These findings are comparable with the findings of the present study.…”
Section: Discussionmentioning
confidence: 84%
“…40% and 44% of the study participants in group A and group B had Moderate degree of anaemia respectively. In a study done by Parikh A et al [11] , 32% patients in the FCM group and 62% in Iron sucrose group had mild degree of anaemia.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Even the risk of allergic adverse reactions, seen with the older IV preparations, are a thing of the past. [30][31][32][33][34][35] Among iron sucrose, ferric gluconate, ferumoxytol, and FCM groups of molecules, the main difference is in pharmacokinetics, dosing, and administration requirements. [36][37][38] The expert group consensus was that FCM provides the most favorable pharmacokinetics and safety profile (it is safe even in patients with history or allergy to other drugs).…”
Section: Discussionmentioning
confidence: 99%
“…In other words, more than 70% of cancer patients are at risk of reduced OS and/or QoL because of CAA. 26…”
Section: Discussionmentioning
confidence: 99%